THE SEDATIVE STUDY OF TABAR KEDAYAN ROOT ETHANOLIC EXTRACT (Aristolochia foveolate) IN MICE (Mus musculus) - Wijayanti, Agustina Dwi; Nugroho, Alvinia Rusandriani; Yanti, Desti Ika; Fitriana, Ida ida (Universitas Syiah Kuala, 2024)
The study was conducted to know the sedation effect of Tabar kedayan (Aristolochia faveolate). Thirty male mice were grouped into six groups, and each group contained five mice which were given six treatments. Group I, II, III, and IV were treated orally with tabar kedayan root ethanolic extract (TKREE) with a single dose of 50, 100, 200, and 400 mg/kg body weight, group V was given chlorpromazine with a dose of 20 mg/kg, and group VI was given distilled water 10 mL/kg of body weight. Based on the analysis, the results of mice falling time for group I, II, III, IV, V, and VI were 238.93101.01, 208.38115.41, 240.69102.19, 276.4268.28, 31.6464.55, and 168.09126.82 seconds, respectively. The groups were significantly different from the positive control group (P0.05). Mice treated with TKREE fell longer than negative and positive controls. Based on these results, the administration of TKREE did not cause a sedation effect on mice; otherwise, may have potential as a stimulant, and studies are needed to provide scientific evidence to support this potential.